Effect of Personalized System for Instructions (PSI) on Physical Fitness of Senior High School nursing's student. (March 2017) - Friskawati, G F; Ilmawati, H; Suherman, A
Abstract: The purpose of this study is to determine the effect of Personalized System for Instructions (PSI) to the physical fitness of Senior High School nursing's student. This research used experimental methods, research design pretest-posttest control group design. A population of 233 of Senior High School nursing's student from Bhakti Kecana at Cimahi, the sample consisted of 25 students for the experimental and control groups has been taken by cluster random sampling. This research was conducted 12 meetings for 4 weeks with a number of meetings three times a week. The instruments used are Tes Kebugaran Jasmani Indonesia (TKJI). Based on the results of data processing and analysis using Paired Samples T tests can be concluded that, There is an effect of Personalized System for Instructions (PSI) to the physical fitness of Senior High School nursing's student with the significant value is 0, 000. Implications of this research shows that to improve the physical fitness of the students, Personalized System for Instructions (PSI) can be used. With notes, the modules at Personalized System for Instructions (PSI) sheet should be easy to understand students.